2002
DOI: 10.1021/jf020310w
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Metalaxyl and Its Pure R-Enantiomer in Sunflower Plants (Helianthus annus)

Abstract: A possible stereospecific and/or stereoselective mechanism of biodegradation for metalaxyl and metalaxyl-M was studied to elucidate their behavior in sunflower plants and to compare their biodegradation. Greenhouse experiments were carried out to confirm the same efficacy of the two fungicides against infections by Plasmopara helianthi in sunflower plants. The two fungicides appear to have the same behavior regarding both the protection against plant infections and the mode of translocation and the rate and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…[3,4] Although the fungicidal activity of benalaxyl and furalaxyl are mainly attributed to their Renantiomer, [5,6] both of them are presently marketed in racemic formulations. Previous studies [7][8][9] have shown that, for chiral pesticides, enantiomers may differ in their activity, toxicity and environmental fate. In these situations, it is necessary to evaluate the behavior of chiral pesticide enantiomers in organisms and the environment, which is beneficial for reducing potential environmental damage from racemic mixtures, and for promoting scientific and rational application of pesticides for the environmental safety and public health.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Although the fungicidal activity of benalaxyl and furalaxyl are mainly attributed to their Renantiomer, [5,6] both of them are presently marketed in racemic formulations. Previous studies [7][8][9] have shown that, for chiral pesticides, enantiomers may differ in their activity, toxicity and environmental fate. In these situations, it is necessary to evaluate the behavior of chiral pesticide enantiomers in organisms and the environment, which is beneficial for reducing potential environmental damage from racemic mixtures, and for promoting scientific and rational application of pesticides for the environmental safety and public health.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] This biological process potentially exposes chiral compounds to stereoselective degradation, and similarly, it can be expected that the behavior and the reaction of these compounds with chiral structures (protein such as metabolizing enzymes) of biological systems (plants) are stereospecific. 3 As far as we know, enantioselective degradation of benalaxyl in the environmental matrix has not been reported. Thus, this research was conducted to determine the stereoselective degradation of the two enantiomers by HPLC-CSP in cucumber plant and several agriculture soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, enantiomers or stereoisomers may have different bioactivity, toxicity, metabolism, excretion, and environmental manner. [2][3][4] In these situations, the evaluation of behavior of chiral pesticides in organisms or in the environment based on the data obtained by achiral analysis methods is not reliable. Therefore, to understand chiral agrochemicals' safety toward environment and public health, it is essential to study the stereoselective degradation of such compounds in the organisms or environment.…”
Section: Introductionmentioning
confidence: 99%
“…The (R)<(S) enantioselectivity in metabolism of aryloxyalkanoic acid herbicides was observed in some plant species including green algae, and similarly in soil metabolism, but with no enantiomerization. 82,[112][113][114][115] Similar enantioselectivity was observed for metalaxyl (10) 89,116) and benalaxyl (11), 91) with no enantiomerization of the former herbicide reported. The simple comparison of soil and plant metabolism may suggest less contribution of enzyme-mediated enantiomerization of these pesticides in plants.…”
Section: Plant Metabolismmentioning
confidence: 69%